Hausmannite Mn3O4 functionalized graphene Oxide-NaClO system for oxidative desulfurization and denitrogenation of fuel oils. (1st August 2022) - Yaseen, Muhammad; Subhan, Sidra; Subhan, Fazle; Ur Rahman, Ata; Naeem, Abdul; Ahmad, Zahoor; Tong, Zhangfa
Graphical abstract: Highlights: Hausmannite Mn3 O4 /GO composite catalyst was synthesized and characterized. Mn3 O4 /GO-NaClO showed ultra-fast (2 min) and efficient (100%) ODS (DBT)/ODN (Py). Active O 2– radicals generated due to synergism between NaClO and Mn3 O4 . Mn3 O4 /GO catalyst remained highly stable and active for six successive reuses. Abstract: Herein, Hausmannite Manganese oxides nanocubes (Mn3 O4 ) deposited on graphene oxide (GO) nanosheets were synthesized and composited together as Mn3 O4 /GO via in-situ on pot hydrothermal technique. To get the morphological and electronic insights, synthesized materials were analyzed via six different analytical procedures including field emission scanning electron microscopy, energy dispersive X-ray elemental mapping, powdered X-ray diffraction, Brunauer-Emmett-Teller surface area, Fourier-transform infrared, and X-ray photoelectron spectroscopy techniques. Mn3 O4 nano cubes were synthesized at an average cube size of 362 nm showing characteristic crystal planes and electronic distribution ratio (Mn 2+ /Mn 3+ ::1:2) of a typical Hausmannite Mn3 O4 structure. Whereas, the synthesized GO sheets (average layer thickness of 451.1 nm) were well consistent with Lerf and Klinowski model and exhibited the characteristic functionalities. Results suggested that incorporation of Mn3 O4 (average particle size of 275.3 nm) at the B-sites of GO enhanced the active surface area by 65 % (22.9 m 2 .g −1 ) and surface functionalities of the composite, which predicted excellent catalytic response from the Mn3 O4 /GO composite. ODS and ODN tests were performed using different substrates of sulfur and nitrogen compounds, where Mn3 O4 /GO-NaClO system removed 2200 ppm DBT and Py in 2 min at 25 °C. O/S and O/N ratio of 4 and 0.04 g/15 mL. Whereas, the overall activity order followed as: DBT (100 %) > 4, 6-DMDBT (89 %) > BT (85 %), and: pyridine (100 %) > indole (83 %) > carbazole (81 %). Recyclability and catalyst stability was recorded for 6th consecutive runs with minimal loss in the activity (100–92 %). High efficiency of the Mn3 O4 /GO-NaClO system was accredited to the ClO − and its propensity of selective synergism with Mn +2 /Mn +3, which the resulted active O 2– that oxidized sulfur and nitrogen species in 2 min at 25 °C. Thus, an alternative route could be obtained for the ultra-fast and highly efficient, environment friendly and cost-effective oxidative desulfurization and denitrogenation of fuel oils.